Community Participation in the Village Fund Direct Cash Assistance (BLT-DD) Distribution Program in Munung Village, Jatikalen Subdistrict, Nganjuk Regency - Asfadina Assabila; Budi Santosa (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze community participation in the Village Fund Direct Cash Assistance (BLT-DD) Program in Munung Village, Jatikalen District, Nganjuk Regency. The focus of the study covers four stages of participation based on the theory of Cohen & Uphoff (1977): decision-making, implementation, utilization of results, and program evaluation. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Informants included the village head, the Village Consultative Body (BPD), the heads of the RT/RW, recipient communities, and non-recipients of BLT-DD. The results showed that at the decision-making stage, participation was carried out through the Village Deliberation (Musdes) forum involving the village government, BPD, and RT/RW. At the implementation stage, participation was realized through the provision of information during data collection and involvement in the distribution process. At the utilization stage, 29 Beneficiary Families utilized the assistance for basic household needs. At the evaluation stage, the community was involved through the Musdes forum to provide responses and input. Overall, community participation takes place through a targeted division of roles between the village government, BPD, RT/RW, and the community, so that program implementation runs transparently and on target.